Words and the mind : how words capture human experience - Malt, Barbara C.; Wolff, Phillip M. (New York ; Oxford : Oxford University Press, 2010)
The study of word meanings promises important insights into the nature of the human mind by revealing what people find to be most cognitively significant in their experience. Here, the authors present evidence on topics as diverse as spatial relations, events, emotion terms, motion events, objects, body-part terms, and more.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Psycholinguistics